Novel Alkyl(aryl)-Substituted 2,2-Difluoro-6-(trichloromethyl)-2H-1,3,2-oxazaborinin-3-ium-2-uides: Synthesis, Antimicrobial Activity, and CT-DNA Binding Evaluations - Rosa, Wilian C.; Rocha, Inaiá O.; Rodrigues, Melissa B.; Coelho, Helena S.; Denardi, Laura B.; Ledur, Pauline C.; Zanatta, Nilo; Acunha, Thiago V.; Iglesias, Bernardo A.; Bonacorso, Helio G. (Frontiers in Pharmacology, 2020)
The synthesis, antimicrobial activity evaluations, biomolecule-binding properties (DNA), and absorption The synthesis, antimicrobial activity evaluations, biomolecule-binding properties (DNA), and absorption and emission properties of a new series of (Z)-1,1,1-trichloro-4-alkyl(aryl)amino-4-arylbut-3-en-2-ones (4,5) and 2,2-difluoro-3-alkyl(aryl)amino-4-aryl-6-(trichloromethyl)-2H-1,3,2-oxazaborinin-3-ium-2-uides (6,7) in which 3(4)-alkyl(aryl) = H, Me, iso-propyl, n-butyl, C6H5, 4-CH3C6H4, 4-CH3OC6H4, 4-NO2C6H4, 4-FC6H4, 4-BrC6H4, 2-naphthyl, is reported. A series of β-enaminoketones (4,5) is synthesized from the O,N-exchange reaction of some amines (3) with (Z)-1,1,1-trichloro-4-methoxy-4-aryl-but-3-en-2-ones (1,2) at 61–90% yields. Subsequently, reactions of the resulting β-enaminoketones with an appropriate source of boron (BF3.OEt2) gave the corresponding oxazaborinine derivatives (6,7) at 50-91% yields. UV-Vis and emission properties of biomolecule-binding properties for the DNA of these new BF2-β-enamino containing CCl3 units were also evaluated. Some compounds from the present series also exhibited potent antimicrobial effects on various pathogenic microorganisms at concentrations below those that showed cytotoxic effects. Compounds 4d, 4e, 6e, and 6f showed the best results and are very significant against P. zopfii, which causes diseases in humans and animals.